Cluster ambidexterity towards exploration and exploitation: Strategies and cluster management - Uwe Cantner; Holger Graf; Michael Rothgang; Tina Wolf (Friedrich Schiller University Jena, 2015)
Cluster studies have shown that innovation can be understood as the result of an inter- organizational process, where a division of labor with regard to exploration and exploitation exists among the actors inside the cluster. A cluster is ambidextrous if it manages to balance innovative activities that exploit existing competencies and is open to novel technological approaches by means of exploration. In this context we are interested in the supportive role of cluster management, assuming that a cluster organization can only persist sustainably if exploitation and exploration are pursued in an appropriate balance. Our analysis is based on surveys that have been conducted between 2011 and 2012 with 10 cluster managements and their respective cluster firms of the first two rounds of the German Leading Edge Cluster Competition. Our results indicate that the demand for services offered by the cluster management depends on companies strategies with respect to exploration, exploitation and ambidexterity. In turn, the priorities set by the cluster management can be explained by the firm needs. Accordingly, we argue that the cluster management acts as a service provider helping the cluster companies to become ambidextrous which in turn makes the cluster as a whole ambidextrous.
Keywords: O30; O32; O38; R11; 330; ambidexterity; cluster; cluster management; exploitation; exploration